The Influence of Job Autonomy, Self-Efficacy, and Compensation on Employee Performance with Job Satisfaction as a Mediating Variable - Dimas Aryo Kusumo; Muhamad Daffa Thareq Arrizky; Audric Radityaputra; Roza Sibarani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
The rapid transformation of the banking industry in the digital era, accompanied by increasing technological demands and a decline in employee numbers at Bank XYZ, has heightened the urgency to understand the determinants of employee performance. Rising turnover rates and fluctuating productivity further underscore the importance of examining organizational and personal factors that shape employee outcomes. This study investigates the impact of job autonomy, self-efficacy, and compensation on employee performance, with job satisfaction as an intervening variable. Using a quantitative survey approach, data were collected from 208 employees at Bank XYZ through questionnaires measuring five key variables. Statistical testing was carried out using multiple regression and mediation analysis. The findings reveal that the three independent variables have a direct positive and significant effect on employee performance. All three also positively and significantly affect job satisfaction. However, the direct effect of job satisfaction on performance was not significant. Mediation analysis further shows that job satisfaction does not mediate the relationships between job autonomy, self-efficacy, and compensation on employee performance. Theoretically, these results challenge established models that position job satisfaction as a critical mediator, suggesting its role may be contingent on industry context. Practically, this indicates that in digitally transforming banks like XYZ, managers should prioritize enhancing direct drivers including autonomy, self-efficacy, and compensation to improve performance, rather than relying on satisfaction as a pathway. The study is limited by its single-bank sample and short observation period, suggesting the need for broader future research.